Fixed Intelligence Mindset, Self-Esteem, and Failure-Related Negative Emotions: A Cross-Cultural Mediation Model - Gál, Éva; Tóth-Király, István; Orosz, Gábor (Frontiers in Psychology, 2022)
A growing body of literature supports that fixed intelligence mindset promotes the emergence of maladaptive emotional reactions, especially when self-threat is imminent. Previous studies have confirmed that in adverse academic situations, students endorsing fixed intelligence mindset experience higher levels of negative emotions, although little is known about the mechanisms through which fixed intelligence mindset exerts its influence. Thus, the present study (Ntotal = 398) proposed to investigate self-esteem as a mediator of this relationship in two different cultural contexts, in Hungary and the United States. Structural equation modeling revealed that self-esteem fully mediated the relationship between fixed intelligence mindset and negative emotions. Furthermore, results of the invariance testing conferred preliminary evidence for the cross-cultural validity of the mediation model. These findings suggest that, students adhering to fixed intelligence beliefs tend to experience greater self-esteem loss when experiencing academic failure, which leads to higher levels of negative emotions.